EKO-TEOLOGI JOHN CALVIN: DASAR KEKRISTENAN DALAM TINDAKAN EKOLOGI (SEBUAH RESPON KEKRISTENAN TERHADAP TINDAKAN EKOLOGI) - Dwi Budhi Cahyono (Diegesis : Jurnal Teologi, 2021)
A question arises how is it possible to act on the ecology of Christian eco-theology resources? There is no denying that there is a connection between direct involvements of Christianity in the world's ecological crisis. a record of the progress of civilization and human science which is moved by the human soul in carrying out the cultural mandate in Genesis 1:28. A strong criticism is given by sociologists, ecologists, and theologians, against the actions of the West in exploiting nature on a large scale which, without being balanced with the protection of nature itself, ultimately results in massive ecological destruction and oblivion. Ecological damage is actually the destruction of mankind. The author tries to give an opinion on how Christianity should support ecological action based on the eco-theology of John Calvin, a Reformed theologian who has long laid the foundation for a Christian ethical view of how Christianity should manage and maintain the existing created nature as a blessing from God for human welfare, as well as the implementation of cultural mandates.